(untitled) (Orinoquia, 2021)
Prochilodus magdalenae is an endemic species of Colombia, it is considered the main species of the Colombian continental fishery due to its catch volumes and relevance for the fishermen’s economy. It is considered an important species for fish farming to food safety. However, due to its feeding habit (iliophagous detritivore) the farming methods is carried out at low stocking densities (<1 fish/m2) in large bodies of water and with low productive performance. Its cultivation is common in association with omnivorous species such as cachamas (Colossoma macropomum, Piaractus brachypomus and Piaractus orinoquensis) and tilapia (Oreochromis niloticus and Oreochromis spp). In an attempt to intensify its cultivation was evaluated with biofloc technology (BFT); for which three stocking densities (5,10, 20 fish/m3) were evaluated for ten months. The results suggest that the stocking density influenced its congrowth, while survival was above 80% in all treatments. During cultivation, P. magdalenae remained at the bottom of the culture tank, where dark-colored organic and inorganic matter was identified, similar to the sludge generated in earthen culture ponds; which suggests that the feeding behavior of the species could influence the low formation of flocs, whose values were lower than those usually reported in BFT. It is concluded that the cultivation of P. magdalenae is possible in BFT, but more research is required to adjust the species to this intensive cultivation system.